Studi Komparatif Motivasi dan Hasil Belajar Ekonomi Siswa Kelas X Peminatan IPS dan Lintas Minat MIPA - Wijayanti, Ni Luh Ayu Ari; Meitriana, Made Ary; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2020)
Purpose this study is to know (1) motivation and economic learning outcomes of specialization students Social Sciences Studies, (2) motivation and learning outcomes of cross-interest economic learning Mathematics and Natural Sciences, and (3) the significant differences between motivation and economic learning students outcomes of specialization Social Sciences Studies and cross-interest Mathematics and Natural Sciences. The design is quantitative study using comparative methods. The population is class X students of specialization Social Sciences Studies and Mathematics and Natural Sciences who had economic cross-interest subjects totaled 332 students with sample taken totaled 192 students. Instruments is used questionnaire and documentation. The data analysis is Independent-Sample T-test. The results is (1) learning motivation economic of specialization students Social Sciences Studies is in the high category and learning outcomes economic are in the sufficient category, (2) learning motivation economic of cross-interest Mathematics and Natural Sciences is in the high category and learning outcomes economic are in the sufficient category, and (3) there are significant difference between motivation and economic learning outcomes in specialization based students Social Sciences Studies and cross-interest based students Mathematics and Natural Sciences.